MANAGING CLASS IN ENGLISH LANGUAGE TEACHING - Aribah, Nila Husnul; Ridwan, Ridwan; Hayati, Hanin Faroh (Pascasarjana Unviersitas Majalengka, 2024)
English learning management is an important thing to pay attention to because it's an important part of the English literacy process. This study aims to determine the learning management used in student English learning in Sunan Ampel Junior High School. Researcher use Qualitative Methodology. Data were collected using observation and interview techniques. The results showed that teacher prepare learning tools such as syllabi, monthly programs, semester programs, and lesson implementation plans. In the implementation of learning, the methods used by teacher are lectures, discussions, questions and answers and assignments. The managing class of the teacher in the english language teaching in Sunan Ampel Junior High School, Teacher first of all as a facilitator. Second, as an organizer. Third, as an evaluator. Fourth, as a facilitator. Fifth, as a participant. The sixth, as resource person. The seventh as tutor. The eighth, as an observer. From this explaining is still 70% that has been applied to the Sunan Ampel Junior High School.